Expression of the F and HN glycoproteins of human parainfluenza virus type 3 by recombinant vaccinia viruses: contributions of the individual proteins to host immunity. - Spriggs, M K (1987)
cDNA clones containing the complete coding sequences for the human parainfluenza virus type 3 (PIV3) fusion (F) and hemagglutinin-neuraminidase (HN) glycoprotein genes were inserted into the thymidine kinase gene of vaccinia virus (WR strain) under the control of the P7.5 early-late vaccinia virus promotor. The recombinant vaccinia viruses, designated vaccinia-F and vaccinia-HN, expressed glycoproteins in cell culture that appeared to be authentic with respect to glycosylation, disulfide linkage, electrophoretic mobility, cell surface expression, and, in the case of the HN protein, biological activity. Cotton rats inoculated intradermally with vaccinia-HN developed serum neutralizing antibody titers equal to that induced by respiratory tract infection with PIV3, whereas animals receiving vaccinia-F had threefold lower neutralizing antibody titers. A single immunization with either recombinant vaccinia virus induced nearly complete resistance in the lower respiratory tract of these animals. With regard to protection in the upper respiratory tract, animals immunized with vaccinia-HN or vaccinia-F exhibited reductions in PIV3 replication of greater than 3,000-fold and 6-fold, respectively. This large difference (greater than 500-fold) in reduction of PIV3 replication in the upper respiratory tract was in contrast to the relatively modest difference (3-fold) in serum neutralizing antibody titers induced by vaccinia-HN versus vaccinia-F. This dissociation between the level of neutralizing antibodies and protection suggested that immunity to PIV3 is complex, and that immune mechanisms other than serum neutralizing antibodies make important contributions to resistance to infection. Overall, under these experimental conditions, vaccinia-HN induced a substantially more protective immune response than did vaccinia-F.